TYPOLOGICAL DIVERGENCE BETWEEN KARAKALPAK AND ENGLISH LANGUAGES (SCIENCE TIME JOURNAL, 2026)
This article conducts a comparative typological analysis of the Karakalpak and English languages in order to identify structural differences that influence the process of formation of foreign language speech. The author explores interlingual interference at the morphological, syntactic and phonological levels, comparing the agglutinative structure of the Karakalpak language with the analytical structure of English. Based on illustrative examples, zones of “linguistic risk” are described, such as the transition from suffixal to prepositional coding, the conflict of word orders SOV and SVO, as well as the influence of the law of synharmonism on the accent-rhythmic pattern of speech.